2004
DOI: 10.1017/s000305540400108x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Validity and Cross-Cultural Comparability of Measurement in Survey Research

Abstract: T he discipline of political science is built on theory, including a rough agreement on normative theories preferring freedom, democracy, and political equality, among others, and the development of positive theories focused on understanding the causes and consequences of these variables. Empirical political science, in turn, is devoted in large part to making causal inferences about these same variables. UnYou may be interested in our Anchoring Vignettes Web site, which, as a companion to this paper, provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 733 publications
(216 citation statements)
references
References 35 publications
3
206
0
7
Order By: Relevance
“…It uses a generalization of the ordered probit model to distribute vector-valued responses according to the proportion of "similar" respondents who choose the categories spanned by the vector. As this approach is not central in the current study, further explanation can be found in King and colleagues (Hopkins & King, 2010;King et al, 2004;.…”
Section: The Technique Of Anchoring Vignettesmentioning
confidence: 83%
See 1 more Smart Citation
“…It uses a generalization of the ordered probit model to distribute vector-valued responses according to the proportion of "similar" respondents who choose the categories spanned by the vector. As this approach is not central in the current study, further explanation can be found in King and colleagues (Hopkins & King, 2010;King et al, 2004;.…”
Section: The Technique Of Anchoring Vignettesmentioning
confidence: 83%
“…The technique of anchoring vignettes was introduced to correct for measurement bias-in particular, the so-called reference-group effect-in Likert-type responses (King, Murray, Salomon, & Tandon, 2004). The reference-group effect stems from different standards (i.e., a reference group) that respondents use to evaluate themselves and their own behaviors, and may be related to various response styles, which refer to the tendency to use certain response options on some basis other than the target construct (Paulhus, 1991).…”
Section: The Technique Of Anchoring Vignettesmentioning
confidence: 99%
“…More robust approaches are required, drawing on experimental designs in which some key elements of the consultation-interaction can be accounted for in the analysis, for example through the use of standardised consultations and video vignettes. 81,82 Using patient survey data to improve care…”
Section: Patients' Varying Experiences Of Carementioning
confidence: 99%
“…To attenuate challenges to inference caused by non-equivalence in measurement, researchers should be careful to evaluate (and report) evidence for the validity of measures before assuming crosscultural equivalence. Such evidence can include techniques modeling response differences (e.g., King et al 2003) Byrne and Campbell 1999). For a more in-depth review, we refer to other work on cross-cultural measurement (e.g., Hui and Triandis 1985;Leung 1997, 2000).…”
Section: Cross-cultural Non-equivalence Of Measurementmentioning
confidence: 99%